EFFICIENCY OF APPLICATION OF THE PREPARATION "E-SELENIUM" AT FARMING OF YOUNG GROWTH OF MINKS OF THE SCANDINAVIAN SELECTION - Яремич, Н. В. (Scientific Progress & Innovations, 2014)
The results of the studies of the impact of selenium preparation "E-Selenium" the dynamics of the live weight of young mink Scandinavian selection. Identified the differences in intensity of growth and development of young animals at various circuits using the preparation "E-selenium." Young mink, which the preparation "E-selenium" was introduced at a dose of 0.04 mg/kg body weight, gaining weight and better exceeded peers in the control group at 180 days of age in '53. Established probable share of influence of selenium preparation "E-selenium» (ηx2 = 0,10-0,24, p <0,01-0,001) on the dynamics of live weight of young minks aged 60-120 days.